2018
DOI: 10.3892/mmr.2018.9128
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive evaluation of differential lncRNA and gene expression in patients with intervertebral disc degeneration

Abstract: The present study aimed to identify novel intervertebral disc degeneration (IDD)-associated long noncoding (lnc)RNAs and genes. The lncRNA and mRNA microarray dataset GSE56081 was downloaded from the Gene Expression Omnibus database and included 5 samples from patients with degenerative lumbar nucleus pulposus and 5 normal controls. Differentially expressed lncRNAs or differentially expressed genes (DEGs) were identified and co-expression network analysis was performed followed by functional analysis for genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…It has been reported that TGFB promotes NP cell proliferation and stimulates ECM synthesis (11). Therefore, overexpression of TGFB may have the potential to inhibit IDD and exert therapeutic effects; this has been demonstrated in several in vivo studies (29,30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that TGFB promotes NP cell proliferation and stimulates ECM synthesis (11). Therefore, overexpression of TGFB may have the potential to inhibit IDD and exert therapeutic effects; this has been demonstrated in several in vivo studies (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicated that targeting the regulatory effects of associated lncRNAs, circRNAs, miRNAs and mRNAs may have a potential role in the clinical treatment of IDD. However, to the best of our knowledge, IDD-associated lncRNA/circRNA-miRNA-mRNA ceRNA regulatory mechanisms remain rarely reported, until now (11).…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge of specific key regulators that support the degenerative process from a molecular perspective should allow for not only better phenotyping of cells, but also developing new regenerative/reparative cell-based or biological therapies for this debilitating condition [3,4,5,31]. In recent years, research on gene expression modulation during both physiological and disease processes of IVD is focusing on attributing critical roles to transcription factors and non-coding RNAs (microRNAs and long non-coding RNAs), not only for what concerns their impact in diverse target genes, but also their interplay [32,33]. We focused here on this aspect and reported, for the first time, that the reciprocal regulation between the transcription factor TRPS1 and miR-221 seems to be of crucial importance for the maintenance of the IVD homeostasis and disc cell functions.…”
Section: Discussionmentioning
confidence: 99%
“…The significant items in the results of enrichment analyses in the present study included 'integrin binding', 'ossification', 'ECM' and 'skeletal system development' Li et al (35) previously reported that the loss of OPG leads to the occurrence of IDD by promoting the 'ossification' biological process of the cartilage endplate in the osteoprotegerin (OPG)-knockout mice. Qu et al (36) reported that DEGs were primarily involved in 'skeletal system development' in a co-expression network in IDD and serve an important role the pathobiology of the disease. A, Genes whose microarray results are consistent with those reported in the literature; B, Genes whose microarray results are inconsistent with those reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the ceRNA mechanism can be used for the analysis of multiple diseases ( 36 , 57 ). Qu et al ( 36 ) constructed a miRNA-lncRNA-mRNA ceRNA regulatory network on the basis of DEGs and lncRNAs in patients with IDD.…”
Section: Discussionmentioning
confidence: 99%